Anatomy and Histochemistry of Alliaceae and Iridaceae Species: Quality Control of Traditional Medicine Raw Materials - Syahruni, Reny; Abdul Halim Umar; Halim, Nur Afiah Ramadhani (Jurnal Jamu Indonesia, 2024)
Alliaceae (Allium cepa and Allium ascalonicum) and Iridaceae (Eleutherine bulbosa) are widely used as spices, condiments, and traditional medicine. These three species are vulnerable to adulteration because they are morphologically similar in shape and colour. This study aims to identify and authenticate the three samples through anatomical and histochemical approaches. Anatomical and histochemical analyses were performed on fresh sections of the bulbs samples according to standard anatomical procedures with a razor blade and identification of the main compound groups using specific reagents. Anatomically, the three samples had similar patterns and cell organelles (cell nucleus, cytoplasm, and cell wall). Histochemical techniques identified the presence of alkaloids, phenolics, lipophilics, and terpenoids groups. Histochemical techniques can be applied in identifying the compound groups of the three samples and can be used as an alternative in testing the quality control of traditional medicine raw materials.